Construction and validation of a list of common Middle Eastern surnames for epidemiological research - Nasseri, Kiumarss (2007)
PURPOSE: Middle Eastern (ME) population is rapidly growing in the US but cannot be easily identified in cancer registry or other databases for epidemiological research. The purpose of this study was to develop a list of common Middle Eastern surnames and validate it by linking with a cancer registry incidence files. METHODS: Surnames and place of birth in the Middle East were obtained from various sources. After exclusion of the non-specific entries, the final combined list included 49,610 surnames and was matched with the California Cancer Registry incidence file for 1988-2003. RESULTS: Overall, 1.4% of all registered cases were positively identified as ME that is similar to the proportion of ME population in California. Two third of the identified cases had known place of birth in the Middle East and of those, 70% were non-Arabs. The sensitivity of the list in detecting ME birth in men and women are 91% and 86%, respectively. The positive predictive values for men and women are 72% and 65%. The specificity and negative predictive values are universally over 99 percent. CONCLUSION: The high accuracy reported for this Middle Eastern surname list (MESL) makes it a valuable tool for epidemiological studies of this ethnic population.